PENGARUH WORK-LIFE BALANCE STRESS KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA (Studi Kasus Pada PT XYZ) - Alif Aulia Sulaeman, (2022)
This research is a quantitative study with the aim of knowing the effect of work life balance, work stress and work environment on job satisfaction at PT XYZ. The total population and sample used are 49 permanent employees of PT XYZ. Researchers collected data by distributing online questionnaires in the form of a Google form. Data analysis techniques using quantitative data analysis using statistical methods. In this study the statistical method used is Partial Least Square (PLS). From the test, the results obtained are (1) work life balance has a positive and significant effect on employee job satisfaction, (2) work stress has a positive and significant effect on employee job satisfaction, (3) the work environment has a positive and significant effect on employee job satisfaction, and (4) work life balance, work stress, and work environment simultaneously have a positive effect on job satisfaction of employees of PT XYZ. Keywords: work life balance, work stress, work environment and job satisfaction